2020
DOI: 10.3762/bjnano.11.130
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and spectroscopic fingerprints of photoactive pyrenyl tectons on hBN/Cu(111)

Abstract: The controlled modification of electronic and photophysical properties of polycyclic aromatic hydrocarbons by chemical functionalization, adsorption on solid supports, and supramolecular organization is the key to optimize the application of these compounds in (opto)electronic devices. Here, we present a multimethod study comprehensively characterizing a family of pyridin-4-ylethynyl-functionalized pyrene derivatives in different environments. UV–vis measurements in toluene solutions revealed absorption at wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
(196 reference statements)
0
5
0
Order By: Relevance
“…We synthesized monolayer hBN on Cu(111) [26,30,36,37] in ultrahigh vacuum (UHV) by first preparing a clean and atomically flat Cu(111) surface via repeated cycles of Ar + sputtering and annealing at 790 K. The Cu(111) substrate was then heated to and maintained at a temperature of ∼1190 K, while being exposed to a partial pressure (∼10 −6 mbar) of borazine (B 3 H 6 N 3 ). The heated Cu(111) surface catalyzes the formation of hBN from the adsorbed precursor borazine molecules.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…We synthesized monolayer hBN on Cu(111) [26,30,36,37] in ultrahigh vacuum (UHV) by first preparing a clean and atomically flat Cu(111) surface via repeated cycles of Ar + sputtering and annealing at 790 K. The Cu(111) substrate was then heated to and maintained at a temperature of ∼1190 K, while being exposed to a partial pressure (∼10 −6 mbar) of borazine (B 3 H 6 N 3 ). The heated Cu(111) surface catalyzes the formation of hBN from the adsorbed precursor borazine molecules.…”
Section: Sample Preparationmentioning
confidence: 99%
“…transition metal dichalcogenides, hexagonal boron nitride [hBN]), with their relatively weak outof-plane chemical reactivity [22], are promising platforms as support for electronically functional low-dimensional molecular nanosystems. Despite these advantages, examples of self-assembly of organic nanostructures (in particular, large-area monocrystalline 2D systems) on these substrates remain limited [23][24][25][26][27][28][29][30][31][32][33][34]. Here, we present low-temperature scanning tunneling microscopy (STM) and spectroscopy (STS) results on the mesoscale 2D self-assembly of a flat aromatic molecule-9,10-dicyanoanthracene (DCA)-on a 2D atomically thin insulator, hBN grown on Cu(111).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the molecular orientation and degree of rehybridization of the first contact layer determine the intrinsic efficiency of charge injection, in terms of alignment of conduction bands and molecular orbitals, as well as chemical and spatial localization of the preferential channel of charge transfer. A combination of structural, morphological, and spectroscopic studies of the interfacial layer at metal substrates is necessary to get insight into the mechanisms governing the formation of thin films: from their assembly to the degree of electronic coupling to the substrate. From this perspective, the use of the orbital mapping based on angle-resolved photoemission (ARPES), together with the support of complementary techniques, such as scanning tunneling microscopy (STM) and low-energy electron diffraction (LEED), allows us to shed light on π-conjugated systems, identifying both the electronic structure of the adsorbates and their geometric arrangement . The momentum distribution of the photoemission intensity can be used to study the orientation of molecules within their unit cell and to disentangle the valence band states stemming from the substrate from those localized on molecules and hence to evaluate the intermolecular and molecule–substrate interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Schaal et al [ 86 ] showed that h BN on Ni(111) electronically decoupled tetraphenyldibenzoperiflanthene such that the molecular vibronic progression was observable by in situ differential reflectance spectroscopy, which is otherwise only achieved for multilayers on the bare Ni. On h BN/Cu(111), Zimmermann et al [ 87 ] could visualize the molecular orbitals of pyrene derivatives by STM at the submolecular level, while Brülke et al [ 88 ] measured the fluorescence of monolayer perylenetetracarboxylic dianhydride (PTCDA), which is quenched on bare Cu(111) and would require three molecular decoupling layers to be probed on Cu(111). In all three studies using h BN, ordered molecular films were observed.…”
mentioning
confidence: 99%
“…In all three studies using h BN, ordered molecular films were observed. The decoupling even allowed for the formation of complex self-assemblies such as kagome lattices by tuning the number and position of the substituents of the pyrenes derivatives [ 87 ].…”
mentioning
confidence: 99%